High levels of oxidized fatty acids in HDL impair the antioxidant function of HDL in patients with diabetes - Feng, Juan; Wang, Yunfeng; Li, Weixi; Zhao, Yue; Liu, Yi; Yao, Xingang; Liu, Shuwen; Yu, Ping; Li, Rongsong (Frontiers in Endocrinology, 2022)
Aims Previous studies demonstrate that the antioxidant functions of high-density lipoprotein (HDL) are impaired in diabetic patients. The composition of HDL plays an important role in maintaining the normal functionality of HDL. In this study, we compared the levels of oxidized fatty acids in HDL from diabetic subjects and non-diabetic healthy controls, aiming to investigate the role of oxidized fatty acids in the antioxidant property of HDL. Methods HDL was isolated from healthy subjects (n=6) and patients with diabetes (n=6, hemoglobin A1c ≥ 9%, fasting glucose ≥ 7 mmol/L)) using a dextran sulfate precipitation method. Cholesterol efflux capacity mediated by HDL was measured on THP-1 macrophages. The antioxidant capacity of HDL was evaluated with dichlorofluorescein-based cellular assay in human aortic endothelial cells. Oxidized fatty acids in HDL were determined by liquid chromatography-tandem mass spectrometry. The correlations between the levels of oxidized fatty acids in HDL and the endothelial oxidant index in cells treated with HDLs were analyzed through Pearson’s correlation analyses, and the effects of oxidized fatty acids on the antioxidant function of HDL were verified in vitro. Results The cholesterol efflux capacity of HDL and the circulating HDL-cholesterol were similar in diabetic patients and healthy controls, whereas the antioxidant capacity of HDL was significantly decreased in diabetic patients. There were higher levels of oxidized fatty acids in HDL isolated from diabetic patients, which was strongly positively correlated with the oxidant index of cells treated with HDLs. The addition of a mixture of oxidized fatty acids significantly disturbed the antioxidant activity of HDL from healthy controls, while the apolipoprotein A-I mimetic peptide D-4F could restore the antioxidant function of HDL from diabetic patients. Conclusion HDL from diabetic patients displayed substantially impaired antioxidant activity compared to HDL from healthy subjects, which is highly correlated with the increased oxidized fatty acids levels in HDL.